Psychiatric Disorders and Weight Change in a Prospective Study of Bariatric Surgery Patients: A 3-Year Follow-Up. Issue 3 (April 2016) - Kalarchian, Melissa A.; King, Wendy C.; Devlin, Michael J.; Marcus, Marsha D.; Garcia, Luis; Chen, Jia-Yuh; Yanovski, Susan Z.; Mitchell, James E.
ABSTRACT: Objectives: To document changes in Axis I psychiatric disorders after bariatric surgery and examine their relationship with postsurgery weight loss. Methods: As part of a three-site substudy of the Longitudinal Assessment of Bariatric Surgery Research Consortium, 199 patients completed the Structured Clinical Interview for DSM-IV before Roux-en-Y gastric bypass or laparoscopic adjustable gastric band. At 2 or 3 years after surgery, 165 (83%) patients completed a follow-up assessment (presurgery median body mass index = 44.8 kg/m 2, median age = 46 years, 92.7% white, 81.1% female). Linear-mixed modeling was used to test change in prevalence of psychiatric disorders over time, report remission and incidence, and examine associations between psychiatric disorders and weight loss. Results: Compared with status presurgery, the prevalence of any Axis I psychiatric disorder was significantly lower at 2 and 3 years after surgery (30.2% versus 16.8% [ p = .003] and 18.4% [ p = .012], respectively). Adjusting for site, age, sex, race, presurgery body mass index, and surgical procedure, presurgery mood, anxiety, eating or substance use disorders (lifetime or current) were not related to weight change, nor were postsurgery mood or anxiety disorders ( p for all > .05). However, having a postsurgery eating disorder was independently associated with less weight loss at 2 or 3 years ( β = 6.7%, p = .035). Conclusions: Bariatric surgery was associated with decreases in psychiatric disorders through 3 years after surgery. Postsurgical eating disorders were associated with less weight loss after surgery, adding to the literature suggesting that disordered eating after surgery is related to suboptimal weight loss. Abstract : Supplemental digital content is available in the text.